دلالات الأفعال في آيات الطُّوفان في قصَّة نوح عليه السَّلام : دراسة وصفيَّة تحليليَّة - قوه، جون جييا شمس الدِّين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This dissertation aims to examine the signification of verbs in Arabic with regard to tense and inflectional morphology. Tense means the semantic time conveyed by the verb to indicate occurrence or recurrence. Inflectional morphology means the root-pattern system that inflects verbs and changes their signification according to their morphological change. The researcher has followed the descriptive analytical approach and has used the Quranic story of Noah and the flood as a model. This is based on the fact that the Quran is the standard of Arabic. To accurately understand the meanings of the Quranic verses, the researcher has additionally used two books of Quranic exegesis; Al-Kashshaaf 'an Haqa'iqat Al-Tanzil by Imam Al-Zamakhsari and Ruh al-Ma'ani fi Tafsir Al-Quran Al-Azim wa Al-Sab'u Al-Mathani by Imam Al-Alusi. The researcher has concluded that a verb is an abstract or concrete occurrence within semantic time. Time in this sense is one of the factors that distinguishes verbs from nouns and other parts of speech. Furthermore, a verb signifies occurrence within semantic time. This signification is regulated by the root-pattern system that regulates verb inflections.